ANALISIS DETERMINAN HARGA SAHAM PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Erni Puji Astutik; Retnosari Retnosari; Ayunda Putri Nilasari (JURNAL ILMIAH EDUNOMIKA, 2021)
The purpose of this study is to analyze the effect of Return On Equity, Current Ratio, and Debt To Equity Ratio on prices in food and beverage companies listed on the Indonesia Stock Exchange. The population of this research is food and beverage companies for the period 2016-2019. Samples were taken by purposive sampling technique. The sample that meets the criteria and can be analyzed is 11 companies from 25 food and beverage companies listed on the Indonesia Stock Exchange in 2016-2019, so that the data collected are 44. The data collection method used is documentation. The data analysis technique used classical assumption test and multiple linear regression analysis. Based on the proposed test using the t test, the key is that (1) Return on Equity has a significant positive effect on stock prices. (2) Current Ratio has no significant effect on stock prices. (3) Debt to Equity Ratio has no significant effect on stock prices. Keywords : ROE, CR, DER, stock price